(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2017)
The essay deals with many problems and difficulties that editors have encountered while working at the volume Poesie, prose e traduzioni by Clemente Rebora. The most outstanding has been to distinguish between literary texts and other kind of writings that previous editions of Poesie (Scheiwiller-Garzanti) had published together: prayers, meditations, pedagogical pieces, occasional verses.